2018
DOI: 10.1096/fj.201800387r
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of thapsigargin– and cyclopiazonic acid–sensitive pumps in the rescue of TMEM165‐associated glycosylation defects by Mn2+

Abstract: Congenital disorders of glycosylation are severe inherited diseases in which aberrant protein glycosylation is a hallmark. Transmembrane protein 165 (TMEM165) is a novel Golgi transmembrane protein involved in type II congenital disorders of glycosylation. Although its biologic function is still a controversial issue, we have demonstrated that the Golgi glycosylation defect due to TMEM165 deficiency resulted from a Golgi Mn2+ homeostasis defect. The goal of this study was to delineate the cellular pathway by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
1
27
1
1
Order By: Relevance
“…We previously reported that LAMP2 glycosylation defects found in TMEM165 KO HEK cells were totally suppressed by the addition of exogenous MnCl 2 in the culture medium. This was observed from 8 hours of incubation with 1 μM MnCl 2 . We recently observed that this suppression could appear without any supplementation of MnCl 2 probably due to cell culture conditions (data not shown).…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…We previously reported that LAMP2 glycosylation defects found in TMEM165 KO HEK cells were totally suppressed by the addition of exogenous MnCl 2 in the culture medium. This was observed from 8 hours of incubation with 1 μM MnCl 2 . We recently observed that this suppression could appear without any supplementation of MnCl 2 probably due to cell culture conditions (data not shown).…”
Section: Resultsmentioning
confidence: 64%
“…This was observed from 8 hours of incubation with 1 μM MnCl 2 . 18,19 We recently observed that this suppression could appear without any supplementation of MnCl 2 probably due to cell culture conditions (data not shown). This urged us to investigate the effects of different sources of FBS on the appearance and/or rescue of the N-glycosylation defects in TMEM165 KO HEK cells.…”
Section: Serum Impacts the Observed Golgi Glycosylation Defects In mentioning
confidence: 90%
See 2 more Smart Citations
“…The Golgi apparatus appears to play an important role in cellular Mn homeostasis and effects on its function often occur over the Mn concentration range used for our studies (Carmona et al 2019;Houdou et al 2019). In fact, previous studies examining Mnregulated proteins included treatments of cells with 1-500 lM Mn over time courses ranging from 1 to 24 h (Masuda et al 2013;Mukhopadhyay et al 2010;Potelle et al 2017;Tewari et al 2015;Towler et al 2000).…”
Section: Discussionmentioning
confidence: 99%